Chronic Fluoride Exposure and the Risk of Autism Spectrum Disorder - Strunecka, Anna; Strunecky, Otakar (International journal of environmental research and public health, 2019)
The continuous rise of autism spectrum disorder (ASD) prevalent in the past few decades is causing an increase in public health and socioeconomic concern. A consensus suggests the involvement of both genetic and environmental factors in the ASD etiopathogenesis. Fluoride (F) is rarely recognized among the environmental risk factors of ASD, since the neurotoxic effects of F are not generally accepted. Our review aims to provide evidence of F neurotoxicity. We assess the risk of chronic F exposure in the ASD etiopathology and investigate the role of metabolic and mitochondrial dysfunction, oxidative stress and inflammation, immunoexcitotoxicity, and decreased melatonin levels. These symptoms have been observed both after chronic F exposure as well as in ASD. Moreover, we show that F in synergistic interactions with aluminum's free metal cation (Al3+) can reinforce the pathological symptoms of ASD. This reinforcement takes place at concentrations several times lower than when acting alone. A high ASD prevalence has been reported from countries with water fluoridation as well as from endemic fluorosis areas. We suggest focusing the ASD prevention on the reduction of the F and Al3+ burdens from daily life.
Keywords: Environmental Exposure; Animals; Autism Spectrum Disorder; ASD prevalence; immunoexcitotoxicity; endemic fluorosis; rizikové faktory; Humans; autism spectrum disorder; socioeconomic status; neurotoxicity; neurotoxické syndromy; fluoridy; lidé; zvířata; Neurotoxicity Syndromes; Fluorides; chronic fluoride exposure; poruchy autistického spektra; Risk Factors; aluminum; vystavení vlivu životního prostředí; water fluoridation